Analisis Metode Perencanaan Dan Pengendalian Persediaan Obat Fast Moving Di Apotek Durikulon - Sri Bintang Sahara Mahaputra Kusuma Negara; Lina Nurna Khumairo; Andini Suryani (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Drug availability is a crucial component of pharmaceutical services to ensure optimal patient care. Inadequate inventory planning and control, particularly for fast-moving drugs, often lead to stock shortages or surpluses that disrupt services and increase operational risks. This study aimed to analyze drug inventory planning and control for fast-moving items at Pharmacy X using consumption methods, Economic Order Quantity (EOQ), safety stock, and reorder point (ROP) approaches. This descriptive quantitative research utilized stock cards and observation sheets as instruments. Data on drug usage, stock availability, and procurement patterns from November 2024 to January 2025 were collected and analyzed. The results showed that applying these methods, such as for Renadinac tablets, produced an optimal procurement plan of 539 tablets, EOQ of 416 tablets, safety stock of 490 tablets, and a reorder point of 791 tablets. Proper planning and inventory control effectively ensured drug availability and optimized stock management.